2004
DOI: 10.1161/01.str.0000132194.24663.3d
|View full text |Cite
|
Sign up to set email alerts
|

A2 Alelle of GpIIIa Gene Is a Risk Factor for Stroke Caused by Large-Vessel Disease in Males

Abstract: Background and Purpose-Glycoprotein IIIa (GpIIIa) is a platelet membrane receptor for fibrinogen and von Willebrand factor. It plays a key role in platelet aggregation. Previous studies in stroke patients, without analysis based on specific subtypes of stroke cause, have not shown any link between GpIIIa A1/A2 polymorphism and stroke risk. We studied the significance of the GpIIIa gene A1/A2 polymorphism in stroke patients with different stroke causes. Methods-We genotyped 92 patients with stroke caused by lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 38 publications
2
31
1
4
Order By: Relevance
“…Homozygosity for MTHFR C677T polymorphism proved to be a significant thrombophilic risk factor in our study, where nine out of the 77 patients were homozygous and none of the 60 controls was found to be homozygous (p=0.005), while the significance of the presence of the A2 allele of GPIIIa gene in the pathogenesis of N-AION in males of our sample is in accordance with the results of Slowik et al [36], which showed that this particular allele may constitute an independent risk factor for some causes of stroke in male population.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Homozygosity for MTHFR C677T polymorphism proved to be a significant thrombophilic risk factor in our study, where nine out of the 77 patients were homozygous and none of the 60 controls was found to be homozygous (p=0.005), while the significance of the presence of the A2 allele of GPIIIa gene in the pathogenesis of N-AION in males of our sample is in accordance with the results of Slowik et al [36], which showed that this particular allele may constitute an independent risk factor for some causes of stroke in male population.…”
Section: Discussionsupporting
confidence: 92%
“…The GPIIIa gene A1/A2 polymorphism of the glycoprotein IIIa on the platelets' surface, caused by a T to C nucleotide substitution at position 1565 on chromosome 17q21, results in increased platelet aggregation and increased thrombotic risk [36], whereas the D/D genotype of angiotensin converting enzyme (ACE) may exert its thrombophilic effect through smooth muscle cell proliferation and plasminogen deficiency due to increase of plasminogen activation inhibitor (PAI) [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…6 All the diagnostic studies related to the stroke evaluation were recorded. Full diagnostic work-up was defined as at least 1 neuroimaging study (CT or MRI), ECG, carotid ultrasound, and echocardiography.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 25% of individuals of Northern European ancestry are PlA2 positive, and only 2% are homozygous for PlA2 (35). This polymorphism has been widely studied in cardiovascular disease, and possession of an A2 allele has been found to increase the risk of myocardial infarction, coronary artery disease, restenosis after stent placement, and stroke caused by large-vessel disease (16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…The genes encoding GPIIb-IIIa are located on chromosome 17q21, and genetic variants can potentially influence both activation of the GP complexes and aggregation itself (14). The PlA1/A2 polymorphism of platelet GPIIIa has been widely studied in cardiovascular disease, and presence of the PlA2 allele has been associated in vitro with increased platelet aggregation and in vivo with ischemic cardiovascular disease (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%